1995
DOI: 10.1074/jbc.270.10.4990
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in Vitro Replication Consequences of Stereoisomeric Benzo[a]pyrene-7,8-dihydrodiol 9,10-Epoxide Adducts on Adenine N6 at the Second Position of N-ras Codon 61

Abstract: Benzo[a]pyrene-7,8-dihydrodiol 9,10-epoxide (BPDE), a metabolite of the widespread environmental pollutant benzo[a]pyrene, is a mutagenic in both bacterial and mammalian systems. Toward understanding the mutagenic effects of different stereoisomers of BPDE at specific sites in DNA, six stereochemically defined BPDE adducts were constructed on adenine N6 at position 2 of the human N-ras 61 codon within an 11-base oligonucleotide fragment. Both the nonadducted and BPDE-adducted N-ras 61 11-mers were inserted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 47 publications
5
89
2
Order By: Relevance
“…Cleavage products containing a trans-S adduct migrated slightly more slowly than did the corresponding fragments containing a trans-R adduct. Differences in electrophoretic migration for oligonucleotides containing R-versus S-BaP DE adducts have been noted previously (31,32).…”
Section: Accumulation Of Top1-mediated Dna Cleavage Complexes By Bap mentioning
confidence: 96%
“…Cleavage products containing a trans-S adduct migrated slightly more slowly than did the corresponding fragments containing a trans-R adduct. Differences in electrophoretic migration for oligonucleotides containing R-versus S-BaP DE adducts have been noted previously (31,32).…”
Section: Accumulation Of Top1-mediated Dna Cleavage Complexes By Bap mentioning
confidence: 96%
“…The stereochemistry of BPDE has an influence on its potent mutagenic and carcinogenic properties (11)(12)(13)(14). It has been shown that BPDE-adducted DNA blocks synthesis by a variety of DNA polymerases (15)(16)(17)(18)(19). Several studies have also demonstrated that BPDE adducts in DNA impede transcription (20 -27).…”
mentioning
confidence: 99%
“…To make a similar correlation with stable adducts, the BPDE-N 6 dA stable adducts should be highly mutagenic and account for the codon 61 A to T mutations. However, the BPDE-N 6 dA adduct does not appear to be exceptionally mutagenic [82] and forms A to G mutations in codon 61 [69].…”
Section: Mutagenesis By Bp and Metabolitesmentioning
confidence: 99%
“…Knowing the mutational specificity in the preneoplastic tissue is important, because it can reveal the critical lesions for cancer. In vitro, the mutational specificity is obtained from studies that examine polymerase errors during the filling synthesis of nicks or gaps similar to those generated by the excision steps of NER and BER [66,67], or those during bypass over PAH-DNA stable adducts (translesion synthesis), similar to those left unrepaired by NER [68,69]. The knowledge obtained from such studies is limited to the specific DNA polymerases, and sometimes cannot explain mutagenesis in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation